Economic Justice Through Al-Hisbah: Reviewing The Role And Performance Of Market Supervisory Institutions - Oktaviandi, M. Rizky; Yogi, Yogi (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This research looks at the role and performance of market supervisory institutions in realizing economic justice through the concept of al-Hisbah. In its background, economic justice is stated as a central issue in sustainable social and economic development, with justice not only an ideal, but also a religious imperative in Islam. The aim of the study is to explore how market supervisory institutions based on al-Hisbah principles play a crucial role in ensuring that economic practices not only benefit a small part, but also support the welfare of society at large. The research method uses a qualitative approach with descriptive analysis, involving literature studies and interviews with economists and practitioners of Islamic law. The results showed that market supervisory institutions that apply the principles of al-Hisbah have a vital role in maintaining a balance between individual and general interests in economic activity. By ensuring that economic practices conform to Islamic principles that emphasize fairness, transparency, and sustainability, such institutions can be effective custodians in achieving the goals of economic justice. This research provides a deeper understanding of how the concept of al-Hisbah can form a solid foundation for creating a more inclusive, just, and sustainable economic system in accordance with Islamic values